Analisis Awal Akhir untuk Merancang Penuntun Praktikum Berbasis Guided Inquiry - Naila Fauza; Dina Syaflita; Ernidawati Ernidawati; Diah Anugrah Dipuja; M. Yogi Riyantama Isjoni; Vebby Oksaviona (SAP (Susunan Artikel Pendidikan), 2022)
Physics is a science that deals with practice. In practicum, it is necessary to be supported by teaching materials, one of which is a practicum guide. Practicum is a learning strategy that allows students to empirically train cognitive, psychomotor, and affective abilities simultaneously by using laboratory facilities. The guided inquiry-based practicum guide is expected to help students in practicum. The purpose of this study is to analyze the beginning and end to design a guided inquiry-based practicum guide. The R and D development model used is the ADDIE model, namely the needs analysis stage, one of which is the front end analysis. This type of research is qualitative research which includes descriptive research. Data collection techniques were a questionnaire. The research was conducted at the University of Riau. The results of the research are lecturers have good teaching performance but need to find a practical guide so as to create a student-centered learning. The practicum guide is prepared based on a needs analysis, namely practicum facilities need to be designed in accordance with the practicum objectives.